2021
DOI: 10.1002/anie.202109465
|View full text |Cite
|
Sign up to set email alerts
|

Functional Switch and Ethyl Group Formation in the Bacterial Polytrichastrene Synthase from Chryseobacterium polytrichastri

Abstract: A reinvestigation of the linalool synthase from Chryseobacterium polytrichastri uncovered its diterpene synthase activity, yielding polytrichastrene A and polytrichastrol A with new skeletons, besides known wanju‐2,5‐diene and thunbergol. The enzyme mechanism was investigated by isotopic labeling experiments and DFT calculations to explain an unusual ethyl group formation. Rationally designed exchanges of active site residues showed major functional switches, resulting for I66F in the production of five more n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 47 publications
1
26
0
11
Order By: Relevance
“…Only here several amino acid residues are smaller than in the SdS active site, which explains why SmTS1 can accept the large substrate GFPP and SdS cannot. Notably, the active site residues are always located in analogous positions, as we have recently summarised in reference [19].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Only here several amino acid residues are smaller than in the SdS active site, which explains why SmTS1 can accept the large substrate GFPP and SdS cannot. Notably, the active site residues are always located in analogous positions, as we have recently summarised in reference [19].…”
Section: Resultsmentioning
confidence: 87%
“…We have recently shown that the sum of the calculated van der Waals volumina (ΣV vdW ) of the active site residues of TPSs can be easily calculated using a simple equation by Abraham and co-workers [18]. They show a clear trend, with the average values being largest for monoterpene synthases (MTPSs, ΣV vdW = 907 ± 24 Å 3 ), and then decreasing for sesquiterpene synthases (STPSs, ΣV vdW = 855 ± 58 Å 3 ) and DTPSs (ΣV vdW = 776 ± 107 Å 3 ), reaching the smallest value for StTPSs (ΣV vdW = 733 ± 79 Å 3 ) [19]. As a consequence, the available active site space will increase from MTPSs to StTPSs to fulfill the increasing space requirements to accommodate the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…After we have made all twenty isotopomers of ( 13 C)GGPP available by chemical synthesis, these materials can be used to efficiently prepare the corresponding twenty isotopomers of diterpenes using diterpene synthases. The obtained compounds can then be studied by 13 C-NMR spectroscopy to follow the incorporation of labelling into the specific positions of diterpenes, which we have done in our previous work for the products of CpPS, [38] allowing for conclusions on the cyclisation mechanism of the enzyme. This is particularly interesting for the diterpenes carrying an unusual ethyl group as observed for polytrichastrene A (1).…”
Section: Discussionmentioning
confidence: 99%
“…1 mg each) were dissolved in aqueous NH 4 HCO 3 solution (1 mL; 25 mm in H 2 O), followed by mixing with Tris buffer (3 mL; 50 mm Tris, 1 mm MgCl 2 , pH = 7.6) and incubation buffer (5 mL; 50 mm Tris, 8 mm MgCl 2 , 8 % glycerol, pH = 7.6). The purified protein solution of CpPS [38] (1 mL) and, if not a labelled GGPP was the substrate, GGPPS [39] (1 mL) were added into the mixture. The solution was incubated at 28 °C overnight and extracted with C 6 D 6 (600 μL + 300 μL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation